Stories of Patient Involvement Impact in Health Technology Assessments: A Discussion Paper. (24th July 2019) - Single, Ann N.V.; Facey, Karen M.; Livingstone, Heidi; Silva, Aline Silveira
Abstract: Objectives: As more health technology assessment (HTA) bodies seek to implement patient involvement, there is a desire to learn from other HTA bodies about their experiences and understand what approaches can be used and which ones make a real difference to HTA. This is difficult, as the impact of patient involvement in HTA is not well documented. This study aims to promote further discussion about the ways in which patient involvement can impact HTAs by studying stories of impact. Methods: In a multi-stakeholder workshop, experts leading patient involvement in four HTA bodies shared examples of HTAs where they believed patient involvement made a difference, then they reflected on these impact stories within the wider context of impact evaluation. Results: The HTA bodies drew on patient input and patient-based evidence to inform their HTAs. The patient involvement was observed to elucidate patients' experiences, needs and preferences which, in turn, was observed to influence the HTA recommendations about optimal use of technologies, including taking account of issues for sub-groups, outcomes that matter to patients and educational needs. Conclusions: Personal stories of patient involvement may enable a wider understanding of different approaches to and impact of patient involvement. The examples relate to both patient input and patient-based evidence and highlight the role that patient involvement can play in reducing uncertainties and complementing the clinical and economic evidence in HTA. They suggest that impact can be seen in recommendations about how and when a technology is used.